Neurocognitive & Ecological Motor Learning Considerations for the 11+ ACL Injury Prevention Program: A Commentary - Dustin R. Grooms; Mario Bizzini; Holly Silvers-Granelli; Anne Benjaminse (North American Sports Medicine Institute, 2024)
The 11+ is a structured warm-up program designed to prevent injuries in soccer players, but has proven efficacy in many populations, settings and sports. It consists of 15 exercises that target the most common injury sites, such as the knee, ankle, and groin. However, the implementation and adherence of the 11+ remain suboptimal, and recent compelling data indicates underlying mechanisms of injury risk related to neural control of movement may not be adequately targeted. Updates to the 11+ considering practical implications of neurocognitive and ecological motor learning may be warranted for coaches and practitioners. We review the evidence on how an updated 11+ may influence the cognitive and perceptual processes involved in motor control and learning, such as attention, anticipation, decision making, and feedback. How the 11+ can be adapted to the ecological constraints and affordances of the football (soccer) environment is also discussed, including the task, the individual, and the context. By considering these factors, the 11+ can be more effective, engaging, and enjoyable for the players, and thus improve its adoption and compliance. The 11+ has the capability to not only a physical warm-up, but also a neurocognitive and ecological preparation for the game. Therefore, the purpose of this manuscript is to describe the conceptual design of a new ecological neurocognitively enriched 11+, that builds on the strong foundation of the original intervention with considerations for the newly discovered potential neural control of movement risk factors.